An Ayurvedic Approach to Inner Ear Diseases - Athira Rosh; Veena Shekar (AYUSHDHARA, 2022)
Ear is one among the sense organs, which keeps one connected to other and with the surroundings. Ear functions the conversion of sound waves into electrochemical impulses and maintains the sense of balance. In the present era, increased technology has resulted in change in lifestyle like increased use of ear phones or headsets, excessive use of mobile phones, exposure to loud noise, and modern pub culture etc which has made the ears more sensitive to many problems. This can be either hearing disorders or tinnitus or vertigo which can have an adverse effect on our lives, which remains the most challenging to treat in contemporary science. Ayurveda gives detailed explanation regarding ear diseases, where in it covers all the diseases pertaining to external as well as internal ear. Therefore, while looking into the classification of these diseases, no such explanation is given separately for Abhyantara karna rogas, but a special attention is given for the explanation of ear lobe diseases (Karna pali rogas). In this article an effort is made to understand these major inner ear problems with those of ear disorders explained in ayurveda with their specific etiology, clinical features and the management with respect to the contemporary science